2020
DOI: 10.3390/su12239790
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Insolvency of SMEs Using Technological Feasibility Assessment Information and Data Mining Techniques

Abstract: The government makes great efforts to maintain the soundness of policy funds raised by the national budget and lent to corporate. In general, previous research on the prediction of company insolvency has dealt with large and listed companies using financial information with conventional statistical techniques. However, small- and medium-sized enterprises (SMEs) do not have to undergo mandatory external audits, and the quality of accounting information is low due to weak internal control. To overcome this probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…For example, the statistics classify rules of decision tree classify algorithm are simple and clear, easy to understand, and difficult to make mistakes in actual operation. By analyzing and summarizing case sets, the decision tree has the ability of multi-concept learning, which is easy to use and has a wide range of apps [ 13 , 14 ]. Decision tree algorithm is a better choice when classifying large-scale case statistics represented by unstructured attribute-value pairs.…”
Section: Research On Statistics Mining Technologymentioning
confidence: 99%
“…For example, the statistics classify rules of decision tree classify algorithm are simple and clear, easy to understand, and difficult to make mistakes in actual operation. By analyzing and summarizing case sets, the decision tree has the ability of multi-concept learning, which is easy to use and has a wide range of apps [ 13 , 14 ]. Decision tree algorithm is a better choice when classifying large-scale case statistics represented by unstructured attribute-value pairs.…”
Section: Research On Statistics Mining Technologymentioning
confidence: 99%
“…Next, the chi-square test was utilized to quantitatively explore whether there is a significant difference between the two groups of drugs by the emergence of adverse reactions during and 24 hours after surgery respectively, for the categorization problem can be listed in the cross-tabulation [9], it was found that the total sample is greater than 40 and the theoretical frequency of each category is greater than 5 available chi-square test:…”
Section: Exploring Quantitative Differences Based On Chi-square Testsmentioning
confidence: 99%
“…But, every company has a slightly different mindset, and therefore a standardized approach to insolvency prevention is a good base but a skilled researcher needs to have the right information about the past, present and the future of a business (Jayasekera, 2018). The keyword and part of the focus in this article are SMEs and in that regard a slightly different approach to insolvency prediction is take due to the nature of SMEs (Lee, Choi and Yoo, 2020).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…In the last few years, there is a growing trend of observing and researching small and medium enterprises as they have always been hard to audit because of their dynamic structure. In the researches of (Camacho-Miñano, Segovia-Vargas and Pascual-Ezama, 2015;Tobback et al, 2017;Lee, Choi and Yoo, 2020) a lot of care is focused on the issues concerning SMEs. This is mainly because many surveyed enterprises are younger than three years, and no relevant data can be collected in that timeframe.…”
Section: Figure 5 Bibliographic Coupling Network Visualization Overlay Visualization Of When Specific Abstract Were Researchedmentioning
confidence: 99%